Throat Spray With Blended Essential Oils Promotes Healthy Lung Function Among Women: A Randomized, Double Blinded, Placebo Controlled Clinical Trial - Jessie Hawkins PhD; Christy Hires MPH, CHES; Elizabeth Dunne MS, RDN; Lindsey Keenan BS, RDN (Journal of Evidence-Based Integrative Medicine, 2022)
Introduction There are numerous internal and external environmental threats to lung health. Compromised respiratory health can affect a person's quality of life. This clinical trial evaluated the effects of Teramune Bronchus on lung health among healthy adult women. Methods The participants were women, aged 18 - 60 years old (n = 35). They sprayed either the proprietary essential oil based blended product (Teramune Bronchus) or a placebo into their throats 4-6 times per day during waking hours for 3 days. There was a baseline survey before using the spray and then follow-up data were collected at the end of day 3. The three primary outcomes for this study include a total bronchial symptom score, the chest domain in the Wisconsin Upper Respiratory Symptom Scale (WURSS), and subjective bronchial wellbeing. Results On day 3, the bronchial health of the participants who received the throat spray had significantly larger change scores when compared those with the placebo spray. All chest-related symptoms were resolved fully by the end of the trial for the participants who used Teramune. Participants using the intervention were almost twice as likely to say they felt better and believed the product helped them achieve lung health. Conclusion This study provides evidence that the use of Teramune Bronchus supports respiratory health. Teramune Bronchus boosts respiratory health among healthy women through the use of plant-based essential oils.